2016
DOI: 10.1016/j.ajog.2015.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Maternal fat, but not lean, mass is increased among overweight/obese women with excess gestational weight gain

Abstract: Background Weight gain in pregnancy is an essential physiological adaptation, supporting growth and development of a fetus, and is distributed among lean mass including total body water, and fat mass gains. Although gestational weight gain provides a source of energy for the mother and fetus, excess gestational weight gain may underlie reported associations between parity and future metabolic disorders, and is linked to postpartum weight retention and insulin resistance. Although weight gain is often proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…Further, our group has already demonstrated that, among overweight/obese women, excess gestational weight gain is comprised of primarily fat, and not fat free, mass. 20 …”
Section: Commentmentioning
confidence: 99%
“…Further, our group has already demonstrated that, among overweight/obese women, excess gestational weight gain is comprised of primarily fat, and not fat free, mass. 20 …”
Section: Commentmentioning
confidence: 99%
“…; Berggren et al . ). Mothers gaining excess weight during pregnancy have a greater probablility of retaining the weight post‐delivery and are at increased risk of obesity, type‐2 diabetes and cardiovascular disease later in life (Frias & Grove, ; Berggren et al .…”
Section: Introductionmentioning
confidence: 97%
“…Of particular concern is the increased risk to the offspring for excess neonatal adiposity and metabolic disease in adolescence and adulthood [3, 4]. Other obesity-related traits, including insulin resistance, are associated with fetal macrosomia [58]. However, the causal nature of the factors that result in higher fetal body adiposity remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%